A mini-review of Chinese contributions to Journal of Molecular Catalysis B: Enzymatic - Xu, Jian-He (Journal of molecular catalysis. B, Enzymatic, 2002)
Since the birth of Journal of Molecular Catalysis B: Enzymatic in 1995, 13 papers contributed from Chinese authors have been published in this journal by the end of year 2001. These papers were summarized in this mini-review by dividing their contents into several subjects, including immobilization of biocatalysts, enzymatic polymerization, asymmetric biocatalysis, non-aqueous biotransformation, and overexpression and stabilization of enzymes. Though the number of annually published papers by Chinese authors in this journal is still very limited, it is increasing rapidly in the recent years.